Macro and micro morphology of the parotid lymph node of neonatal indigenous and crossbred piglets - Sarma, M; Kalita, S N; Goswami, R N; Sarma, K K (The Indian Journal of Animal Sciences, 2011)
The parotid lymph node of indigenous and crossbred piglets was located near the mandibular joint, ventrorostral to the extel1lal ear and medial to the parotid salivary gland. The colour varied from cream to brown. The shape varied from elongated to oval. It was smooth in group I, further elongated in group 2, appearance of fissures in group 3, which deepened to form 2 unequal nodes in group 4 of each variety. Micro morphologically the parotid lymph nodes were structurally inverted; the cortex was present in the central zone and medulla at the periphery in all the age groups. These nodes were invested by connective tissue capsule from which connective tissue fibres penetrated the organ as trabeculae. Both capsule and trabeculae were made of mainly collagen fibres. Few reticular fibres and a poor population of elastic fibres were also observed. Smooth muscle cells were also present. Primary lymphatic nodules were present in all the age groups but secondary lymphatic nodules were present from group 2 onwards. The cell population of the germinal centre consisted of lymphoblasts, few macrophages along with reticular and plasma cells.